Pentingnya Budaya Organisasi Berbasis Islam Sebagai Pengaruh Mediasi Terhadap OCB-IP - Rhienta Aprisella (Studi Ilmu Manajemen dan Organisasi, 2025)
Purpose: The purpose of this study is to explore the relationship between Islamic spirituality in the workplace, affective commitment, and Organizational Citizenship Behavior in Islamic Philanthropic Organizations (OCBIP). Specifically, the research aims to investigate the mediating role of Islamic-based organizational culture in enhancing OCBIP among employees. Methodology/approach: This research employs a quantitative approach utilizing Structural Equation Modeling (SEM) to analyze the data collected from 144 employees working in Islamic philanthropic organizations in Indonesia uses a survey method and the data was processed using AMOS software. Results/findings: The findings indicate that there is no direct influence of Islamic spirituality on OCBIP or affective commitment on OCBIP. However, the study reveals that Islamic-based organizational culture significantly influences OCBIP. Furthermore, the mediating role of Islamic-based organizational culture is confirmed, demonstrating a significant effect between Islamic spirituality in the workplace and affective commitment towards OCBIP. Conclusions: The study concludes that Islamic spirituality and affective commitment do not directly influence Islamic-based OCB, but both have indirect effects through Islamic organizational culture. Strengthening organizational culture rooted in Islamic values is essential to enhance employee behavior and performance. Limitations: Focus on an Islamic perspective and philanthropic organizations in Indonesia. Thus, the findings may not be generalizable to other types of organizations or cultural settings. Contribution: Literature on organizational behavior by highlighting the importance of Islamic-based organizational culture in promoting OCBIP. The findings offer practical implications for Islamic philanthropic organizations, suggesting that cultivating an organizational culture aligned with Islamic values can enhance employee engagement and performance.